Structural Analysis of Chloroquine Resistance Reversal by Imipramine Analogs - Bhattacharjee, Apurba K. (American Society for Microbiology, 2001)
For imipramine, desipramine, and eight analogs of these well-known drugs, an N-5-aminoalkyl substitution was a minimum but insufficient structural feature associated with chloroquine resistance reversal. Although a second distal aliphatic nitrogen atom was unnecessary for resistance reversal, the direction of the dipole moment vector was critical.